Students’ Anxiety in Facing Objective Structured Clinical Examination - Simbolon, Pomarida; Simbolon, Nagoklan (Proceeding International Conference on Religion, Science and Education, 2024)
Anxiety is a feeling of restlessness and fear in response to an unclear threat to something caused by anticipation of danger and signals that help individuals to take action to overcome the threat. Anxiety can happen to anyone, including students, and is a problem that needs to be addressed, because it will have an impact on students’ performance in taking practical exams. OSCE is a practical exam with assessments based on skills observed while carrying out various skills that are able to evaluate many skills in a strict and disciplined manner. OSCE has many benefits, but OSCE raises students’ feelings of anxiety. The aim of this research was to determine the anxiety picture of STIKes Santa Elisabeth Medan students in facing the Objective Structured Clinical (OSCE). The method used is a descriptive approach. The research sample consisted of 62 people using a total sampling technique. The instrument used was a questionnaire. Data analysis using univariate. The research results showed that 44 people (70.9%) had severe levels of anxiety when facing the OSCE, 12 people (19.4%) had mild anxiety, and 6 people (9.7%) had moderate levels. Students need to be given information before carrying out the OSCE so that they can reduce the level of anxiety when facing the exam. The research results showed that 44 people (70.9%) had severe levels of anxiety when facing the OSCE, 12 people (19.4%) had mild anxiety, and 6 people (9.7%) had moderate levels. Students need to be given information before carrying out the OSCE so that they can reduce the level of anxiety when facing the exam. The research results showed that 44 people (70.9%) had severe levels of anxiety when facing the OSCE, 12 people (19.4%) had mild anxiety, and 6 people (9.7%) had moderate levels. Students need to be given information before carrying out the OSCE so that they can reduce the level of anxiety when facing the exam. Early preparation and better organization is needed to promote its evaluative efficacy.